Housing projects in Algeria: which context for which consequences on built environments? Case of Zerhouni City in Algiers / Lilia Makhloufi - Makhloufi, Lilia (Faculty of Architecture, Planning & Surveying and UiTM Press, 2013)
The term sustainable development includes human development, values and cultures. We are referring to sustainable human development in order to emphasize issues such as the importance of housing quality and participation in decision-making process. Offering many dwellings, the new urban spaces in Algeria are supposed to respond today's population needs, their construction capacity is important, they are aired and endowed of important facilities. But, are they really a place where people want to live, now and in the future? What about urban harmony and wellbeing in this case? Starting from the macro to arrive to the micro, we will consider, in this paper, housing projects in Algeria while analysing the old and the new built environments in Algiers, a representative example at the national scale when it comes to housing and the case of Zerhouni city in particular, one of its nearest and recent suburban area.